Can sodium bicarbonate intake contribute to judo fights performance? - Artioli, G. G.; Coelho, D. F.; Benatti, F. B.; Gailey, A. C.; Gualano, B.; Lancha Jr, A. H. (Revista Brasileira de Medicina do Esporte, 2006)
The objective of this study was to investigate the effect of the NaHCO3 ingestion on the judo performance. Six male athletes ingested 0.3 g x kg1 body weight of NaHCO3 or CaCO3 (placebo) 2 h before 3 fights of 5 min, with 15 min recovery. Immediately afterwards, and 15 min after each fight, the athletes related their perceived exertion. The blood lactate concentration was verified in rest, after warming up, 0, 3, 5, 7, 10 and 15 min after each fight. The same experimental protocol was repeated twice by each athlete, except for the ingested substance. The study adopted the counterbalanced double-blind model. There was no significant difference for the performance variables. The perceived exertion did not differ among the treatments, and the blood lactate concentration was significantly greater (p < 0.05) after NaHCO3 ingestion in the first moments of the protocol. In conclusion, the ergogenic effects of NaHCO3 are not enough to contribute to the improvement of the performance in judo fights. However, the model limitations must be considered when generalizing these results. Future studies should use other tools to evaluate the performance in judo.